2022
DOI: 10.26441/rc21.1-2022-a14
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la actividad política en redes sociales durante la primera vuelta electoral de las elecciones generales 2021 en Perú

Abstract: Las elecciones generales de 2021 en Perú se desarrollaron en un contexto inusual generado por diversos factores. Además de realizarse en el año del bicentenario de la independencia del país y de contar con dieciocho candidatos presidenciales, el proceso electoral estuvo marcado por una profunda crisis política y por la pandemia de la COVID-19. En este contexto, la presente investigación tiene como objetivo comprender cómo se gestionó la comunicación política de los candidatos y sus partidos políticos en las re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…The very few studies focusing on political campaigns found that in Ecuador TikTok's presence has helped new or marginal candidates get in the spotlight (Muñoz, 2021). In Peru, Montúfar-Calle et al (2022), analyzing candidates' adoption of different social networks, have concluded that keeping up with new cultural and technological innovations is still an unfinished business for most Peruvian politicians, while Calderón et al (2022), examining only Conservative candidates, have disclosed that they have used TikTok mostly to fuel social division and to disseminate a polarizing discourse.…”
Section: Tiktok and Political Communicationmentioning
confidence: 99%
See 3 more Smart Citations
“…The very few studies focusing on political campaigns found that in Ecuador TikTok's presence has helped new or marginal candidates get in the spotlight (Muñoz, 2021). In Peru, Montúfar-Calle et al (2022), analyzing candidates' adoption of different social networks, have concluded that keeping up with new cultural and technological innovations is still an unfinished business for most Peruvian politicians, while Calderón et al (2022), examining only Conservative candidates, have disclosed that they have used TikTok mostly to fuel social division and to disseminate a polarizing discourse.…”
Section: Tiktok and Political Communicationmentioning
confidence: 99%
“…Considering the importance of the young cohorts in the electoral census-one-third of the Peruvian voting population, 6,928,324, is represented by citizens under the age of 30 years-and the increasing popularity of TikTok, it is no surprise that politicians have adopted this social network to connect with the younger audience (Montúfar-Calle et al, 2022).…”
Section: Social Media and Politics In Perumentioning
confidence: 99%
See 2 more Smart Citations
“…Con respecto a las campañas electorales versadas en estos espacios, históricamente se señala la campaña electoral de Barack Obama como la primera llevada a cabo con el uso masivo de redes sociodigitales. Obama utilizó Facebook y Twitter para conectar con otros usuarios votantes y así llegar a la presidencia de Estados Unidos en 2008 (Montúfar-Calle et al, 2022). Este suceso abrió las puertas para que los estudiosos de los fenómenos de internet y las coyunturas políticas, la opinión pública, los medios y los políticos giraran su foco a las campañas electorales online.…”
Section: De La Esfera Lúdica a La Esfera Públicaunclassified